Deciphering Age Differences in Experience-Based Decision-Making: The Role of Sleep - Peng, Xue-Rui (Nat Sci Sleep, 2020)
OBJECTIVE: Recent studies have demonstrated that sleep not only facilitates memory consolidation but also benefits more complex cognitive skills such as decision-making in young adults. Older adults use different decision strategies compared with young adults, which leaves the role of sleep in older adults’ decision-making unclear. We investigated the age-by-sleep effect on decision-making. METHODS: We recruited 67 young adults (ages 18 to 29 years) and 66 older adults (ages 60 to 79 years) and randomly assigned them into the “sleep” or “wake” study condition. They were given a modified Iowa gambling task to perform before and after a 12-hour interval with sleep or wakefulness. RESULTS: Using the typical model-free analysis, we found that young adults’ between-session performance improved greater than that of older adults regardless of the sleep/wake condition. Furthermore, older adults with longer total sleep time showed a greater improvement in the selection of one “good” deck. To further examine the sleep effect on age-related differences in cognitive processes underlying decision-making, we conducted computational modelling. This more fine-grained analysis revealed that sleep improved feedback sensitivity for both young and older adults while it increased loss aversion for older adults but not for young adults. CONCLUSION: These findings indicate that sleep promotes learning-based decision-making performance via facilitating value representation, and such modulation is distinct in young compared to older adults.